Human Rights at the Intersections Transformation through Local, Global, and Cosmopolitan Challenges - Gruskin, Sofia; Banai, Hussein; Mahdavi, Pardis; Chase, Anthony Tirado (Bloomsbury Academic, 2022)
Addresses local versus cosmopolitan debates regarding human rights through the foregrounding of the lived realities of human rights activists and movements.